Intensive Care in Ulcerative Gastroduodenal Hemorrhages - E. V. Nedashkovsky; S. V. Spiridonov; V. G. Ivanova (Общая реаниматология, 2008)
Objective: to retrospectively evaluate the efficiency of using an algorithm of intensive medical therapy for ulcerative gastroduodenal hemorrhage (UGDH). This algorithm combines earlier initiation of intensive care, identification of groups at increased risk for poor outcomes of hemorrhage, endoscopic treatment, and the present-day antisecretory treatment regimens using proton pump inhibitors (PPI). Subjects and methods. The authors analyzed 108 cases of intensive therapy for UGDH at two emergency care hospitals in 2005—2006, including 57 patients from intensive care units (ICU) who received antisecretory therapy with parenteral ^-histamine blockers and 51 patients who took par-enteral PPI. The Rockall scale was used to predict the outcome of treatment and to determine needs for intensive care. The formed groups were similar in age, gender, the pattern, frequency, and nature of comorbidity, the sources and severity of hemorrhage, and the level of blood loss on admission. Results. The rates of recurrent hemorrhages and deaths were significantly higher among high-risk patients having a Rockall Score of 5 or more. As compared ^-histamine blockers, the use of PPI showed a reliable and clinical significant (39.3%) reduction in the rate of recurrences in high-risk patients. The frequency of emergency operations for a relapse reduced by 18.1%, the duration of ICU treatment and the mean length of hospital stay decreased by 23.7 hours and 2.5 days, respectively. Red blood cell transfusion volume showed a 25% reduction per dose. Overall mortality, a need for surgery, and the length of hospital stay remained unchanged. Conclusion. The study has provided evidence for the predictive value of the Rockall scale in determining a relapse and a fatal case in patients with UGDH and demonstrated the higher efficiency of prevention of recurrent hemorrhage during ICU treatment with PPI versus ^-histamine blockers. Key words: ulcerative gastro-duodenal hemorrhage, Rockall scale, proton pump inhibitors.